2013
DOI: 10.6061/clinics/2013(09)13
|View full text |Cite
|
Sign up to set email alerts
|

Phytoestrogen α-zearalanol ameliorates memory impairment and neuronal DNA oxidation in ovariectomized mice

Abstract: OBJECTIVE:The aim of this study was to evaluate the effect of a novel phytoestrogen, α-Zearalanol, on Alzheimer's disease-related memory impairment and neuronal oxidation in ovariectomized mice.METHODS:Female C57/BL6 mice were ovariectomized or received sham operations and treatment with equivalent doses of 17β-estradiol or α-Zearalanol for 8 weeks. Their spatial learning and memory were analyzed using the Morris water maze test. The antioxidant enzyme activities and reactive oxygen species generation, neurona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Studied in different cell lines, ZEN exhibited competitive inhibitor properties on aromatase or CIP19, inhibiting the biosynthesis of estrogen [ 16 ]. On the other hand, other studies reported the positive effects of ZEN on hippocampal neurogenesis and cognitive improvement in ovariectomized mice and rats, similar to those caused by 17β-estradiol (E2) [ 17 , 18 , 19 ]. The neuroprotective effects of ZEN metabolites were also demonstrated in cultured primary hippocampal neurons exposed to amyloid-β peptide (25–35) [ 20 ].…”
Section: Introductionmentioning
confidence: 98%
“…Studied in different cell lines, ZEN exhibited competitive inhibitor properties on aromatase or CIP19, inhibiting the biosynthesis of estrogen [ 16 ]. On the other hand, other studies reported the positive effects of ZEN on hippocampal neurogenesis and cognitive improvement in ovariectomized mice and rats, similar to those caused by 17β-estradiol (E2) [ 17 , 18 , 19 ]. The neuroprotective effects of ZEN metabolites were also demonstrated in cultured primary hippocampal neurons exposed to amyloid-β peptide (25–35) [ 20 ].…”
Section: Introductionmentioning
confidence: 98%
“…Dong et al. () evaluated the effect of α‐ZAL on Alzheimer's disease‐related memory impairment and neuronal oxidation in ovariectomised female mice exposed to equivalent doses of 17β‐oestradiol or α‐ZAL for 8 weeks. Mice received i.p.…”
Section: Toxicitymentioning
confidence: 99%